Vegetation, hydrological and morphological dynamics of natural islands in the Danube Delta - Chirila, Simona Dumitrita (Hacquetia, 2025)
The Danube Delta is a unique ecosystem located in southeastern Romania. Within this ecosystem, hydrological and morphological dynamics have an important role in maintaining biodiversity. The study aimed to analyze the vegetation, hydrological factors, and morphological dynamics of seven islands in the Danube Delta. The study was carried out during 2023–2024 at Isaccea (three islands), Dunavă? (three islands) and Dranov (one island) in all four seasons. Phytocoenological relevés were carried out for the vegetation analysis, and the SonTek RiverSurveyor M9 equipment was used for the hydrological analysis. The analysis of island dynamics was carried out through morphometric methods, using ANCPI orthophotos (2004 and 2021) and Landsat satellite images (2010). In the seven islands, six associations from the Artemisietea vulgaris, Lemnetea, Phragmito-Magnocaricetea, and Salicetea purpureae classes were found. The hydrological analysis indicated seasonal fluctuations in water level, flow, and velocity, with significant increases in the autumn and winter, especially at Isaccea. The hydrological regime has an important role in the morphodynamic modelling of the Danube Delta islands, indicating the river’s ability to induce rapid transformations through sedimentation and erosion processes. The island’s location influences this interaction, the river flow dynamics and human interventions such as the rectification of meanders.
Keywords: alluvial islands; aluvialni otoki; Danube river; Donava (vodotok); hidrologija; hydrology; mokrišča; wetlands